GAMBARAN SELF ESTEEM SISWA YANG BERASAL DARI ORANGTUA SINGLE PARENT - Rabiatul Adawiyah; Nurfarhanah; Dina Sukma; Soeci Izzati Adlya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Self-esteem is an important aspect of adolescent psychological development that can influence various aspects of life, including academic achievement, social relationships, and mental health. This study aims to describe the self-esteem of students from single-parent families. This study uses a descriptive approach with quantitative methods. The subjects of this study were junior high school students from single-parent families, selected using total sampling technique. The instrument used for data collection was the self-esteem scale based on Coopersmith's theory. The results of the study showed that the self-esteem of students from single-parent families was in the moderate category. To enhance students' self-esteem, counseling services that can be provided include information services, individual counseling services, and group counseling services.